PERANCANGAN SISTEM MONITORING DANA BANTUAN UNTUK PETANI DENGAN MENGGUNAKAN WATERFALL DAN MODELLING VIEW CONTROLLER (MVC): STUDI KASUS: KABUPATEN BOJONEGORO - Ali Akbar, Fawwaz; Nugroho, Budi; Sri Indrawanti, Annisaa (Universitas Islam Balitar, 2022)
Design is important in the process of developing a system. With the design process, we can design the needs of a system according to the specifications of the user's needs. The result of design process will later be used as a guideline in the system implementation stages. The problem raised in this study is the process of monitoring aid funds for farmer groups in Bojonegoro District. Government assistance funds for agriculture are distrbuted from the District Agriculture and Food Security Service to Farmer Groups. Then, the Farmers Group will distribute the funds to the farmers. The distribution of funds from Farmer Groups to farmers has the potential for fraud. This is due to the lack of monitoring by the local government in the process of distribution funds from Farmer Groups to farmers. From the description of the problem of distribution funds by farmer groups, it is necessary to design a system for the distribution and use of aid funds for farmer groups. For the system development process use the waterfall development method. The waterfall approach was chosen because the waterfall method is carried out in stages and has good system development documents at each stage. With the waterfall method, the design process can be carried out in-depth because there is no overlap with other processes. The results of this study are in the form of design artifacts which include use case diagrams, activity diagrams, system architecture, class diagrams, database design, and interface design.